Determinants of financial stability on real estate companies in the Indonesian stock exchange from 2012 – 2022 - Santoso, Herry; Atahau, Apriani Dorkas Rambu; Ugut, Gracia Shinta S; Hulu, Edison (International Journal of Management and Sustainability, 2025)
This study aims to empirically analyze the impact of profitability (PRFT), leverage (LEVG), liquidity (LIQD), firm age (FAGE), interest rate (INTR), firm value (FVAL), firm size (FISZ), and COVID-19 (COVD) on the financial stability (FSTA) of real estate companies listed on the Indonesia Stock Exchange from 2012 to 2024. Using secondary data, the research adopts a purposive sampling method to select companies based on predefined criteria, with the final sample drawn from 83 registered real estate firms. The F-statistic test was performed, and the results were identical for Model 1 and Model 2, confirming that all independent variables—PRFT, LEVG, LIQD, FAGE, INTR, FVAL, FISZ, and COVD collectively influence financial stability (FSTA). In Model 1, the individual significance test (t-test) revealed that LEVG, LIQD, FAGE, INTR, FVAL, and FISZ significantly affect FSTA, while PRFT and COVD do not. Conversely, in Model 2, PRFT, LEVG, LIQD, FAGE, FVAL, and FISZ were found to significantly impact FSTA, whereas INTR and COVD showed no effect. Finally, in Model 3, PRFT, LEVG, and LIQD do not mediate their respective effects on FSTA. The research model remains robust despite two adjustments to the independent variables. The first adjustment incorporates the Financial Stability Index (FISI), while the second adjustment still incorporates FISI, but COVD is removed.